Efektivitas Antipiretik Ekstrak Daun Sawo Manila (Manilkara Zapota (L.) P.Royen.) pada Mencit Putih Jantan (Mus Musculus) yang Diinduksi Pepton 5% - Rifda Naufa Lina; Annis Rahmawaty; Pika Yulia Indriatama (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Fever is a secondary effect of infection (bacteria, viruses, parasites) or other diseases characterized by an increase in body temperature above normal temperature, which is 36-37oC. Fever can be treated with antipyretic drugs, one of which is paracetamol. Previous studies have shown that Manilkara zapota (L.) contain flavonoids, saponins and tannins that work by inhibiting the cyclooxygenase enzyme, thereby inhibiting the process of prostaglandin formation, so that body temperature will decrease. This study aims to determine the antipyretic effectiveness of 96% ethanol extract of Manilkara zapota (L.) on male white mice (Mus musculus L.) induced with 5% peptone. This study is an experimental study with a pretest-posttest with control group design. The test animals used were 25 male white Swiss Webster mice and were divided into 5 groups: negative control (CMC-Na), positive control (paracetamol), treatment group (extract dose of 100, 200, and 400 mg/kgBW). Antipyretic testing was carried out by measuring the rectal temperature of mice before and after induction of 5% peptone as much as 1 mL subcutaneously using a digital thermometer for an interval of 30 minutes to 150 minutes. The results of the study were analyzed by One-Way ANOVA with Post Hoc LSD test so that the optimal dose was obtained in lowering the body temperature of mice 400 mg/kgBW.